Factors influencing time-dependent decannulation after pediatric tracheostomy according to the Kaplan-Meier method - Falla, Patricia I.; Westhoff, Jens; Bosch, Nikolaus; Federspil, Philippe A. (European archives of oto-rhino-laryngology and head & neck, 2020)
The aim of this study was to determine whether there were differences in decannulation rates and time to decannulation in children depending on the indication for tracheostomy, age, and maturity at birth.
Gesehen am 07.09.2021